2019
DOI: 10.15376/biores.14.4.9531-9543
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on some characteristics of Scots pine (Pinus sylvestris L.) wood

Abstract: Heat treatment of wood materials is generally performed to improve the physical, mechanical, chemical, surface, thermal, and crystallinity characteristics. In this way, the usage areas of wood material in different purposes can be expanded by means of heat treatment. The goal of this study was to determine the physical, mechanical, chemical, crystallinity, and surface properties of heat-treated Scots pine (Pinus sylvestris L.) wood. The test samples were heat-treated at 120 °C, 150 °C, 180 °C, and 210 °C for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
5
6
0
Order By: Relevance
“…Therefore, the density was reduced (Vital et al 1983). Regarding the change in wood density, similar results were reported by Durmaz et al (2019). He deems that the removal of volatile extracts and moisture in the wood will cause the decrease of density.…”
Section: Analysis Of the Influence Of Extractive On The Mechanical Properties Of Pine Woodsupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, the density was reduced (Vital et al 1983). Regarding the change in wood density, similar results were reported by Durmaz et al (2019). He deems that the removal of volatile extracts and moisture in the wood will cause the decrease of density.…”
Section: Analysis Of the Influence Of Extractive On The Mechanical Properties Of Pine Woodsupporting
confidence: 77%
“…According to the research conclusions of Vital et al (1983) and Durmaz et al (2019), it can be known that the degradation of wood chemical components will lead to decrease of wood density. Surprisingly, the fillings materials (extractives and hemicellulose, etc.)…”
Section: Analysis Of the Influence Of Extractive On The Mechanical Properties Of Poplar Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Sahin Kol et al (2009) it was stated that the decrease in EMC values due to the decrease of total hydroxyl groups and the decrease of free hydroxyl groups related to chemical change after heat treatment. Durmaz et al (2019) measured the changes in the physical properties of the heat treated wood whereby the density and EMC declined with increase treatment conditions. In a similar study, Bal (2015) reported that after heat treatment, the density and EMC values of wood decreased.…”
Section: Resultsmentioning
confidence: 99%
“…This method improves wood properties without addition of any chemical substance. Within the scope of thermal modification, many types of wood, different temperatures, heating rate and durations have been studied to determine the optimum process conditions (Syrjänen and Kangas 2000;Zaman et al 2000;Militz 2002;Mazela et al 2003;Esteves et al 2007;Kesik et al 2017;Durmaz et al 2019).…”
Section: Introductionmentioning
confidence: 99%